Kdm6b Haploinsufficiency Causes ASD/ADHD-Like Behavioral Deficits in Mice - Gao, Yuen; Aljazi, Mohammad B.; He, Jin (Frontiers in Behavioral Neuroscience, 2022)
Autism spectrum disorder (ASD) is a neurodevelopmental disease that has intellectual disability (ID) and attention deficit/hyperactivity disorder (ADHD) as its common comorbidities. Recent genetic and clinical studies report that KDM6B, a gene encoding a histone H3 lysine 27-specific demethylase, is one of the highest ASD risk genes. However, the relationship between KDM6B mutations and neurodevelopmental diseases remains unclear. Here we use an animal model to show that genetic deletion of one Kdm6b allele in mice leads to autistic-like impaired sociability and object recognition memory. In addition, the mutant mice display markedly increased locomotor activity and impulsivity, two ADHD-like behavioral traits that are ameliorated by methylphenidate treatment. Thus, our study not only uncovers a potential causal link between disruptive KDM6B mutations and ASD/ADHD-like behavioral deficits, but also provides a new mouse model for studying the cellular and molecular mechanisms underlying the Kdm6b-mutation-related neurodevelopmental diseases.